Influence of Li-TCNQ impurities on dielectric properties of planar-oriented nematic liquid crystal - Vovk, V.E.; Kovalchuk, O.V.; Kovalchuk, T.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
The dielectric properties of planar-oriented nematic liquid crystal E25M with Li-TCNQ impurities have been investigated within the frequency range 10–1…106 Hz and temperatures 298…343 K. The concentration of impurities varied between 0 and 0.1 wt.%. It has been shown that the presence of a small impurity of Li-TCNQ in liquid crystal increases electrical conductivity, influences the value of the conductivity activation energy in the nematic phase, and practically does not change the activation energy in the isotropic phase. The times of dielectric relaxation τ for the low-frequency part of the spectrum of complex dielectric constant components have been estimated. It has been shown that, within the frame of existence of the liquid crystal phase, the temperature dependence of τ–1 linearly depends on the inverse value of the temperature in the Arrhenius coordinates and agrees well with the temperature dependence of conductivity.